Comparison of MR Imaging Findings between Extraligamentous and Subligamentous Disk Herniations in the Lumbar Spine - Oh, K.-J. (AJNR Am J Neuroradiol, 2013)
BACKGROUND AND PURPOSE: The method of treating an HIVD in the lumbar spine may depend on the integrity of the PLL. The purpose of this study was to analyze and compare the MR imaging findings of extraligamentous and subligamentous HIVDs in the lumbar spine. MATERIAL AND METHODS: One hundred seventeen patients (M/F = 71:46; mean age, 47 years; age range, 15–79 years) underwent lumbar spine MR imaging and disk surgery (extraligamentous/subligamentous = 66:51) from May 2003 to November 2006. Two radiologists in consensus retrospectively reviewed all MR images, focusing on 10 criteria. RESULTS: The following 5 criteria are suggestive of extraligamentous HIVD in the lumbar spine: 1) spinal canal compromised for more than half its dimension, 2) internal signal difference in the HIVD, 3) an ill-defined margin of the HIVD, 4) disruption of the continuous low-signal-intensity line covering the HIVD, and 5) the presence of an internal dark line in the HIVD (P < .05). When we combined these 5 MR imaging criteria, the sensitivity, specificity, accuracy, and odds ratio were 77.3%, 74.5%, 76.1%, and 9.93 (P < .0001). CONCLUSIONS: Our proposed 5 MR imaging criteria will be helpful in differentiating extraligamentous and subligamentous HIVDs in the lumbar spine.